Learning AutoCAD Civil 3D 2010 : using hands-on exercises, explore the essential elements for creating, analyzing, and managing civil engineering drawings and projects (Autodesk, 2009)
"This beautiful full-color Official Training Guide from Autodesk is the perfect resource for those just starting out or for professionals seeking to improve their Civil 3D skills or preparing for Civil 3D certification. Written by those who know Civil 3D inside and out-Autodesk experts who helped create the software-this full-color book thoroughly covers essential topics and concepts, and then reinforces your learning with pages of real-world drawings and examples"--Resource description page.